A Process-Oriented Framework of Moral Development in Early Childhood Collaborative Learning: A Structured Literature Review - Riyana Widiyawati; Edwita Edwita; Tjipto Sumadi (CV. Gerasi Insan Nusantara, 2026)
Moral behaviour in early childhood represents a crucial dimension of holistic development; however, the processes through which it is formed remain insufficiently articulated, particularly in light of children’s still-developing capacities for self-regulation and reflection. While collaborative learning is widely acknowledged for enhancing social and cognitive competencies, its contribution to moral development is often taken for granted rather than critically examined. This study seeks to explore how collaborative learning supports the emergence of moral behaviour in early childhood education through a structured literature review guided by PRISMA principles. The findings suggest that moral development does not arise automatically from participation in collaborative activities, but is shaped through three interconnected processes: social interaction, which introduces children to multiple perspectives; negotiation and regulation, which enable them to manage differences and adjust behaviour; and reflective internalisation, through which social experiences are gradually integrated into personal moral understanding. Based on these insights, the study proposes a process-oriented conceptual framework that explains how moral behaviour is constructed within collaborative learning contexts. The study offers a theoretical contribution by questioning assumptions of automatic moral development and by providing a conceptual basis for understanding how moral learning unfolds in socially mediated environments.